Phenotypic and genetic analyses of two Campylobacter fetus isolates from a patient with relapsed prosthetic valve endocarditis. Issue 9 (28th December 2021) - Lynch, Caoimhe T; Buttimer, Colin; Epping, Lennard; O'Connor, James; Walsh, Niamh; McCarthy, Conor; O'Brien, Deirdre; Vaughan, Carl; Semmler, Torsten; Bolton, Declan; Coffey, Aidan; Lucey, Brigid
ABSTRACT: Campylobacter fetus can cause intestinal and systemic disease in humans and are well-established veterinary and economic pathogens. We report the complete genomic sequences of two C. fetus subsp. fetus (Cff) isolates recovered in 2017 (CITCf01) and 2018 (CITCf02) from a case of recurrent prosthetic valve endocarditis. Both were capable of growth aerobically. Their genomes were found to be highly conserved and syntenic with 99.97% average nucleotide identity (ANI) while differences in their respective sap loci defined the temporal separation of their genomes. Based on core genome phylogeny and ANI of 83 Cff genomes belonging to the previously described human-associated Cff lineage, CITCf01 and CITCf02 grouped in a clade of 11 sequence type (ST)3 Cff (including the Cff type strain NCTC 10842 T ). CITCf01 and CITCf02 were marked for their lack of unique genomic features when compared to isolates within the subspecies and the type strain in particular. We identified point mutations in oxidative stress response genes, among others, that may contribute to aerobiosis. We report a case of Cff causing relapsed prosthetic valve endocarditis and we highlight the sap island as a polymorphic site within the genetically stable ST3 lineage, central to pathogenicity. Abstract : Molecular mechanisms that govern antigenic variation in C. fetus contribute to relapsed infection, and subtle genetic differences confer unusual ability to grow in air.